“They are not criminals”. Infractions, legislation and internment detention of underage men (San José, Costa Rica, 1955-1973) - Izquierdo Vázquez, Carlos (2022)
The article analyzes the detention measures for male minor offenders. Law 3260 transformed the treatment of minors, seeking to differentiate it from the processing of adults while the Juvenile Court was in charge of their legal defense. Since the 1960s, young men detained in the Luis Felipe González Flores Orientation Center predominated. The social workers took over the intervention, the treatment and the accompaniment of the detained minors and their families. The success of the rehabilitation and re-education policies was described by lawyers and social workers as low due to the lack of an institutional budget, the inadequate detention facilities, the insufficient number of social workers, the absence of an intermediate center and the lack of specialized care measures.